Predictors of post-traumatic stress disorder among ambulance personnel in the western cape province - Ntatamala, Itumeleng Mmoko Theophelus (Department of Public Health and Family Medicine, 2022)
Objective: To determine the factors associated with an increased risk for PTSD in ambulance personnel and the barriers faced in accessing support for work related stress (WRS). Methods: A cross-sectional study of voluntary participants comprising 388 ambulance personnel was conducted. Participants completed self-administered questionnaires: Impact of Event Scale-Revised (IES-R), EMS Critical Incident Inventory (CII), EMS Chronic Stress Questionnaire (EMSCSQ), SF-36 Quality of Life questionnaire (SF-36) and Connor-Davidson Resilience Scale (CD-RISC) which were used to assess PTSD and level of occupational stressors. Results: The prevalence of PTSD in the study population was 30%. Participants were predominantly female (55%), median age 38 (IQR; 31 - 44) years with a professional qualification (83%). Those with PTSD were more likely current smokers (OR=1.76, 95% CI: 1.05 - 2.95), current illicit drug users (OR=16.4, 95% CI: 1.87 - 143.86) and problem drinkers (OR=3.86, 95% CI: 1.80 - 8.23). A self-reported mental health condition (OR=3.76, 1.96 - 7.21), being treated for a medical condition (OR=1.95, 1.22 - 3.11), exposure to chronic WRS (OR=1.05, 1.04 - 1.07) and high critical incident stress score (OR=1.03, 1.02 - 1.04) were positively associated with PTSD risk. Barriers to seeking help for WRS included concerns that services were not confidential, and that the participant's career would be negatively affected. Conclusion: The PTSD prevalence in ambulance personnel is considerably higher than that found in previous studies conducted among this occupational group in the Western Cape. Identified risk factors should inform interventions designed to support ambulance personnel and a greater focus on addressing barriers to accessing care is needed.